Experiences of Teaching the Heat Energy Topic in English as a Second Language - Halim, L.; Dahlan, F.; Treagust, David; Chandrasegaran, Arulsingam (International Council of Associations for Science Education (ICASE), 2012)
In view of the current debate in Malaysia about the teaching of science and mathematics in English, a qualitative study was undertaken involving a purposeful sampling of three non-physics teachers to ascertain how well equipped they were with the necessary pedagogical content knowledge relating to the teaching of the topic of 'heat energy' in the second language (i.e., English) to cater to the needs of Year 10 students of diverse interests and abilities in the subject. Data were obtained using video recordings from I 0 classroom observations of the teaching and learning of the following topics/concepts: (I) thermal equilibrium, (2) heat capacity, (3) specific heat capacity, (4) latent heat, (5) specific latent heat, and (6) Boyle's Law, Charles' Law and the Pressure Law. This video analysis was triangulated using data from interviews with the three teachers. The findings revealed that the teachers possessed a variety of instructional strategies to teach the concepts in English and displayed commendable ingenuity to further facilitate student understanding by explaining in the Malay language when students experienced difficulty, while at the same time insisting that students used the appropriate English terms. In addition, when not familiar with certain physics apparatus, the teachers opted for simulations of the relevant experiments. As a result, the study has introduced a new component to PCK, i.e., the role of a second language in teaching science.